GRAVITATIONAL MICROLENSING AND EXTENDED SOURCE MODELS - Sliusar, V. M.; Zhdanov, V. I. (Одеські астрономічні публікації, 2014)
We perform statistical simulations of light curves of extended microlensed sources having different brightness distribution in the source plane. We generated a set of realizations of lensing point mass system that takes into account an external shear; these include 12000 point masses which are uniformly distributed in the lens plane. The list of the circular symmetric source models used includes gaussian, limbdarkening, power law and Shakura-Sunyaev accretion disk models observed face-on. We estimated difference η between the amplification curves (an analog of the light curves) for these different source models. This difference appears to be considerable, in some cases it amounts up to ∼ 10%. However, the effect of theshear within limits = 0 ÷ 0.5 is not considerable, though it leads to some diminishing of η.